Procesos emisores de fotones en dispersión de electrones - Soto-Vargas, C. W. (2011)
The investigations involving the scattering cross sections arising in virtual and real photon emission processes of electron and positron scattering by an atomic nucleus, have the need for thorough and complete calculations of the virtual photon spectrum and the bremsstrahlung related radiation tail. We make a complete review of the plane wave calculations and the introduce the distorted wave formulation, which is mathematically involved and numerically elaborated, but accesible to its use in experimental electron scattering facilities.